2008
DOI: 10.1093/humrep/dem403
|View full text |Cite
|
Sign up to set email alerts
|

Paternal age and adverse birth outcomes: teenager or 40+, who is at risk?

Abstract: Teenage fathers carry an increased risk of adverse birth outcomes that is independent of maternal confounders, whereas advanced paternal age is not an independent risk factor for adverse birth outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
3
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 33 publications
7
81
3
3
Order By: Relevance
“…Several retrospective studies from Canada and the USA showed no effect of advanced paternal age (Basso and Wilcox, 2006;Olshan et al, 1995), whereas pregnancies induced by fathers younger than 20 years had a higher risk for preterm birth. This was confirmed in a recent retrospective cohort study of nulliparous women aged 20 -29 years in the USA (Chen et al, 2008), where the preterm births in couples with teenage fathers were more frequent when compared with fathers aged 20-29 years (OR 1.15, 95% CI: 1.1, 1.2). The evaluation of older men did not reveal any influence of age on birth outcomes.…”
Section: Preterm Birthsupporting
confidence: 54%
See 1 more Smart Citation
“…Several retrospective studies from Canada and the USA showed no effect of advanced paternal age (Basso and Wilcox, 2006;Olshan et al, 1995), whereas pregnancies induced by fathers younger than 20 years had a higher risk for preterm birth. This was confirmed in a recent retrospective cohort study of nulliparous women aged 20 -29 years in the USA (Chen et al, 2008), where the preterm births in couples with teenage fathers were more frequent when compared with fathers aged 20-29 years (OR 1.15, 95% CI: 1.1, 1.2). The evaluation of older men did not reveal any influence of age on birth outcomes.…”
Section: Preterm Birthsupporting
confidence: 54%
“…In a large retrospective US study, paternal age below 20 is associated with adverse birth outcome as low APGAR scores, low birthweight, increased risk for small-for-gestational-age births and neonatal mortality (Chen et al, 2008), whereas the same study found no influence of higher paternal age. This is in contrast with the Danish study showing a slightly increased risk for lower 1 and 5 min APGAR values in fathers older than 45 years compared with fathers 20 -29 years of age.…”
Section: Paternal Age and Outcome Of Offspringmentioning
confidence: 87%
“…These findings suggest that other critical paternal sociocultural, sociodemographic factors may be at play that could not be assessed because of the limitations of the data set used in this analysis. Previous studies have indicated that an association exists between paternal race/ethnicity (Krishnakumar et al, 2011;Palomar, DeFranco, Lee, Allsworth, & Muglia, 2007), education (Blumenshine, Egerter, Libet, & Braveman, 2011;Bray, Gunnell, & Smith, 2006;Chen et al, 2008;Kiernan, 1997;Saikh et al, 2011), support and involvement (Alio et al, 2011;Alio, Kornosky, Mbah, Marty, & Salihu, 2010;Ghosh, Wilhelm, Dunkel-Schetter, Lombardi, & Ritz, 2010), and alcohol, tobacco, and drug use (Chen et al, 2008;Little & Sing, 1986;Vine, 1996) and adverse feto-infant outcomes. Consequently, it may be beneficial for interconception care, which incorporates prenatal care, to include both mothers and fathers to prevent or minimize health problems for mother and child (Johnson et al, 2006;Mercer et al, 1999;Surkan, Stephansson, Dickman, & Cnattingius, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are a variety of important limitations affecting these findings, including the lack of information on the role of important sociodemographic factors, including maternal smoking status, prenatal care, and race/ethnicity. The effect of young paternal age on feto-birth outcomes has been less documented; however, a previous study found younger paternal age to be associated with an increased risk of preterm birth, low birth weight, small size for gestational age, low Apgar score, neonatal mortality, and postneonatal mortality (Chen et al, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…Pregnancies fathered by men aged 50 or more years (n5124) had almost twice the risk of ending in a fetal loss compared with pregnancies with younger fathers (hazard ratio51.88; 95% confidence interval: 0.93-3.82), after adjustment for maternal age, reproductive history and maternal lifestyle during pregnancy. Chen et al 84 have performed a retrospective cohort study of 2 614 966 live singletons born to women aged 20-29 years and estimated the independent effect of paternal age on adverse birth outcome. Teenagers (,20 years old) had an increased risk of low birth weight (OR51.13) preterm birth (OR51.15), small-for-gestational-age births (OR51.17), low Apgar score (OR51.13), neonatal mortality (OR51.22) and postneonatal mortality (OR51.41).…”
Section: Birth Defectsmentioning
confidence: 99%